Fuentes y bibliografía para el estudio de las instituciones documentales parlamentarias españolas en el siglo XIX - Fernández Bajón, M.ª Teresa (Revista General de Información y Documentación, 2002)
The present work gathers together the basic sources and bibliographyfor the documental study of the Spanish parliamentary records institutions which date from the XIX century. To this end, without going into the history of these institutions which result from this century´s information and records policy, we make a start with some brief annotations of the same and finish with an account of the sources and bibliography for their study.